The contribution of CXCL12-expressing radial glia cells to neuro-vascular patterning during human cerebral cortex development - Errede, Mariella; Girolamo, Francesco; Rizzi, Marco; Bertossi, Mirella; Roncali, Luisa; Virgintino, Daniela (Frontiers in Neuroscience, 2014)
This study was conducted on human developing brain by laser confocal and transmission electron microscopy to make a detailed analysis of important features of blood-brain barrier microvessels and possible control mechanisms of vessel growth and differentiation during cerebral cortex vascularization. The blood-brain barrier status of cortex microvessels was examined at a defined stage of cortex development, at the end of neuroblast waves of migration and before cortex lamination, with blood-brain barrier-endothelial cell markers, namely tight junction proteins (occludin and claudin-5) and influx and efflux transporters (Glut-1 and P-glycoprotein), the latter supporting evidence for functional effectiveness of the fetal blood-brain barrier. According to the well-known roles of astroglia cells on microvessel growth and differentiation, the early composition of astroglia/endothelial cell relationships was analysed by detecting the appropriate astroglia, endothelial, and pericyte markers. GFAP, chemokine CXCL12, and connexin 43 (Cx43) were utilized as markers of radial glia cells, CD105 (endoglin) as a marker of angiogenically activated endothelial cells, and proteoglycan NG2 as a marker of immature pericytes. Immunolabeling for CXCL12 showed the highest level of the ligand in radial glial fibres in contact with the growing cortex microvessels. These specialized contacts, recognizable on both perforating radial vessels and growing collaterals, appeared as CXCL12-reactive en passant, symmetrical and asymmetrical vessel-specific RG fibre swellings. At the highest confocal resolution, these RG varicosities showed a CXCL12-reactive dot-like content whose microvesicular nature was confirmed by ultrastructural observations. A further analysis of radial glial varicosities reveals colocalization of CXCL12 with connexin Cx43, which is possibly implicated in vessel-specific chemokine signalling.